Synthesis and characterization of poly(ethylene glycol)‐based thermo‐responsive polyurethane hydrogels for controlled drug release. (19th August 2013) - París, Rodrigo; Marcos‐Fernández, Ángel; Quijada‐Garrido, Isabel
<x xml:space="preserve">Abstract</x> The thermo‐responsiveness, swelling and mechanical properties of a series of novel poly(ester‐ether urethane) hydrogels have been investigated. These thermo‐sensitive hydrogels were obtained by combining hydrophobic biodegradable poly(ε‐caprolactone) diols and hydrophilic two‐, three‐ and four‐arm hydroxyl terminated poly(ethylene glycol) (PEG) of various molecular weights, using hexamethylene diisocyanate, dichloroethane as solvent and a tin‐based catalyst. The use of multifunctional PEGs leads to the formation of covalent crosslinking points allowing an additional control of the swelling capability. Thus, it was found that tuning the hydrophilic/hydrophobic balance and the crosslinking degree by changing the composition, the swelling and the thermo‐responsive behavior of these hydrogels could be modulated. The obtained hydrogels showed a volume transition at around room temperature. Therefore, and taking into account their biocompatibility, these hydrogels show promising properties for biomedical applications, such as drug delivery. Thus, the loading and release of diltiazem hydrochloride, an antihypertensive drug used as model, were investigated. These new PEG polyurethane hydrogels were able to incorporate a high amount of drug providing a sustained release after an initial burst effect. Copyright © 2013 John Wiley & Sons, Ltd.